2012
DOI: 10.1136/bmjspcare-2012-000262
|View full text |Cite
|
Sign up to set email alerts
|

Quality of advance care planning policy and practice in residential aged care facilities in Australia

Abstract: ObjectivesTo assess existing advance care planning (ACP) practices in residential aged care facilities (RACFs) in Victoria, Australia before a systematic intervention; to assess RACF staff experience, understanding of and attitudes towards ACP.DesignSurveys of participating organisations concerning ACP-related policies and procedures, review of existing ACP-related documentation, and pre-intervention survey of RACF staff covering their role, experiences and attitudes towards ACP-related procedures.Setting19 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 36 publications
3
38
0
Order By: Relevance
“…The questions on knowledge, attitudes and practice were modelled on past ACP HP surveys. 21 The content of the survey items were reviewed by ACP facilitators from the RPC program and quality improvement facilitators from the PCOC program to ensure they were understandable and applicable to palliative care services.…”
Section: Survey Toolsmentioning
confidence: 99%
“…The questions on knowledge, attitudes and practice were modelled on past ACP HP surveys. 21 The content of the survey items were reviewed by ACP facilitators from the RPC program and quality improvement facilitators from the PCOC program to ensure they were understandable and applicable to palliative care services.…”
Section: Survey Toolsmentioning
confidence: 99%
“…After all, it is the one certainty in healthcare -we will all die. And yet, Bill Sylvester and his colleagues found, in 2012, that only two thirds of health professionals had a level of comfort dealing with discussions around Advance Care Plans and only 24% reported that in the last 6 months they had discussions about Advance Care plans with all/most/some residents in aged care facilities [3]. If we aren't talking about what we want -how will anyone know when it comes to the end of our life?…”
Section: Editorialmentioning
confidence: 99%
“…Existing LTC data suggest that policies and procedures related to ACP are limited and the quality of the existing ACP documentation is poor [30]. The perspectives of LTC residents, their families, and substitute decision-makers are particularly lacking to guide ACP quality improvement strategies [31], thus making it a priority to explore what is most important to them in EOL decision-making [32].…”
Section: Introductionmentioning
confidence: 99%